Long-Term Effects of Instilled Mineral Dusts on Pulmonary Surfactant Isolated from Monkeys - C. L. Schengrund; X. Chi; J. Sabol; J. W. Griffith (The National Institute for Occupational Safety and Health (NIOSH), 1996)
"Experiments were carried out to determine the long-term effect of instillation of 500 mg of generic bituminous, anthracite, quartz, or titanium dioxide (Ti02) dust on the composition of pulmonary surfactant. Dust was instilled in the caudal lobe of the right lungs of female pigtailed macaque monkeys (Macaca nemestrina). The composition of surfactant isolated from cell-free bronchoalveolar lavage (CF-BAL) samples obtained from right lungs (dust exposed) at various times over the following year was compared with that of surfactant isolated from CF-BAL from left lungs (dust free) . Little change was seen in the amount of surfactant-associated lipid phosphorus as a result of exposure to dust. Exposure to quartz, anthracite, or Ti02 dust induced a significant increase in the total amount of protein in the surfactant-enriched fraction. The relative amount of specific proteins was also altered: surfactant-associated protein A decreased, and the amount of the heavy and light chains of immunoglobulin molecules (identified by NHiterminal amino acid sequence analysis) increased. These changes were visible more than a year after instillation of quartz and at least 3 months after instillation of anthracite dust. Despite variation in the responses of the individual animals, the changes observed might serve as an indicator of the severity of the effect of exposure of the lung to mineral dust and/or to pathogens. IntroductionSurfactant is essential for normal pulmonary function and gas exchange. It functions to reduce surface tension and may help to prevent pulmonary edema [19] and to protect against infection [13]. The importance of surfactant to normal Jung function is illustrated by the fact that neonates lacking appropriate surfactant undergo respiratory distress and do not survive without clinical support."